Dynamic Rearrangement Compression Algorithm for Intelligent Connected Vehicles - Wu, Yujing; Li, Jinze; Xu, Yinan; Chung, Jin-Gyun; Dai, Yilin; Xu, Yihu (IEEE transactions on vehicular technology, 2022)
The intelligent vehicle terminal T-BOX of intelligent connected vehicles (ICVs) is directly connected to the vehicle interface and constantly exchanges real-time data inside and outside the vehicle, which significantly increases the communication pressure on the in-vehicle network. Excessive data will increase the load on the channel due to the limited bandwidth of the vehicle. Although the existing data compression algorithm can effectively reduce the communication pressure, it requires significant driving data to count the number of signal changes, which increases the preliminary labor cost. Meanwhile, it is difficult to meet the stable compression rate using a static configuration when a large amount of CAN data is transmitted with fluctuating data changes, which cannot satisfy the requirement of reducing the bus load rate, and satisfying the real-time requirements of ICV is challenging. Thus, we propose a real-time dynamic data compression algorithm for vehicles to satisfy such requirements. The experiments show that for the frequently changing signals, the proposed algorithm can improve the compression rate by about 10% compared with the existing compression algorithm. The execution time of the compression process is 4.55 μs at a clock frequency of 400 MHz and the decompression process execution time is 86.48 μs. Compared with the bus load when the original message is transmitted, the proposed algorithm can reduce the bus load by 19% on average. In the future, a stable compression rate will be crucial when loading authentication codes on the CAN to ensure its security.